2016
DOI: 10.3390/molecules21111572
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Structure-Activity Relationships of Novel Diaryl Urea Derivatives as Potential EGFR Inhibitors

Abstract: Two novel series of diaryl urea derivatives 5a-i and 13a-l were synthesized and evaluated for their cytotoxicity against H-460, HT-29, A549, and MDA-MB-231 cancer cell lines in vitro. Therein, 4-aminoquinazolinyl-diaryl urea derivatives 5a-i demonstrated significant activity, and seven of them are more active than sorafenib, with IC 50 values ranging from 0.089 to 5.46 µM. Especially, compound 5a exhibited the most active potency both in cellular (IC 50 = 0.15, 0.089, 0.36, and 0.75 µM, respectively) and enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…In fact, the suppression of EGFR signaling abolishes the acquisition of oocyte developmental competence 34,35 . Previous studies have reported that the MAPK pathway and the EGFR signaling are inhibited by urea and its derivatives [9][10][11]36 . Oyamada et al reported that, based on the form of in vitro culture (IVC, i.e., individual-IVC or in group-IVC), the presence of EGF in the maturation medium changes differently the early embryonic development in bovines 33 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, the suppression of EGFR signaling abolishes the acquisition of oocyte developmental competence 34,35 . Previous studies have reported that the MAPK pathway and the EGFR signaling are inhibited by urea and its derivatives [9][10][11]36 . Oyamada et al reported that, based on the form of in vitro culture (IVC, i.e., individual-IVC or in group-IVC), the presence of EGF in the maturation medium changes differently the early embryonic development in bovines 33 .…”
Section: Discussionmentioning
confidence: 99%
“…6 a). In view of the fact that the EGF may inhibit AAs transport 23 , it is proposed that the increased depletion of AAs by COCs can result from the inhibiting action of urea on the EGF/EGFR system 9 11 . COCs were matured in the presence of NAC in order to test the potential interactive effect of urea on AAs metabolism via EGFR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic compounds containing the phenylurea unit are known to be valuable in terms of biological activity (Jiang et al, 2016;Sikka et al, 2015). As part of our studies in this area, we new report the crystal structure ( Fig.…”
Section: Structure Descriptionmentioning
confidence: 99%
“…On the other hand, among the compounds exhibiting biological activity, it known that compounds containing the diarylurea unit have a broad spectrum of activity. [ ][ ] There are many studies in the literature that reveal antimicrobial, anticonvulsant, anti‐inflammatory, antiplasmodial, antidepressant, antiviral, antituberculosis, and cytotoxic activities of the diarylurea containing compounds. Also sorafenib IV and linifanib V, [ ][ ] which are used in the treatment of cancer, are good examples of bioactive compounds containing the diarylurea unit ( Fig.…”
Section: Introductionmentioning
confidence: 99%